Civil society in Ukraine: stages of formation and new initiatives community - Череватюк, Вікторія Богданівна; Безпальча, Олена Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In recent years greatly increased interest of scientists to the problems of civil society in Ukraine, especially in terms of analysis of European experience. With the development of society, its transition from lower to higher level, so does the state. With improvement of society the state becomes democratic, it has developed democracy, economic freedom, freedom of the citizen, and with the formation of a civil society state becomes legal. Problems associated with the formation and development of civil society do not lose their relevance, because in recent years in Ukraine were appeared a modern forms and practices of self-organization of citizens, the most common of which is volunteer battalions and volunteers organization. The activities of these associations we can surely called a method of maintaining and strengthening universal values, the implementation rights and responsibilities of citizens, personal growth through the realization of human potential. Flexible forms of voluntary activities in practice were the most productive, because bypassing of the bureaucratic procedures in extraordinary circumstances led to the saving time and sometimes even saving lives. Actually, we can’t ignore the role of volunteer battalions, what in the most difficult time for the country acted for the defense of national sovereignty and independence. This article is devoted analyzing of the views of scientists on civil society, its development and formation, reviewed the interaction of public initiatives with public authorities and investigated the newly created forms of self-organization in Ukraine.